Morfologia do estômago do cervo-do-pantanal (Blastocerus dichotomus, Illiger 1815) - Machado, M. R. F. [UNESP]; Leal, L. M. [UNESP]; Sasahara, T. H. C. [UNESP]; Oliveira, F. S. [UNESP]; Duarte, J. M. B. [UNESP]; Okuda, H. T. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2015)
Based on the lack of information regarding the morphology of marsh deer, this work aims to describe some morphological aspects of the gastric chamber in this species, collaborating with future investigations, mainly related to rational handling in this cervid. This work aimed to describe the morphology of the gastric chamber of the marsh deer, characterizing the external and internal macroscopical details and the microscopical architecture of these structures by light microscopy. Macroscopically, the marsh deer stomach is formed by the rumen, reticulum, omasum and abomasum similar to the domestic ruminants. Microscopically, rumen and abomasum are similar to the domestic ruminants. The reticulum and the omasum, however, present specific characteristics such as keratin on the top of the reticulum, small epithelial projections and omasum folds covered with discrete papillae.

Em razão da falta de informações sobre a morfologia do cervo-do-pantanal, objetivou-se apresentar a morfologia das câmaras gástricas desse cervídeo. Macroscopicamente, o estômago do cervo-do-pantanal é formado pelo rúmen, retículo, omaso e abomaso, assemelhando-se aos ruminantes domésticos. Microscopicamente, o rúmen e o abomaso são semelhantes aos animais domésticos, já o retículo e o omaso apresentam características específicas, como acentuada queratinização no ápice das pequenas projeções epiteliais do retículo e pregas omasais revestidas por discretas papilas.
Morphology of the marsh deer's stomach (Blastocerus dichotomus, Illiger 1815)
Keywords: Anatomy; Wild animal; Cervid; Digestory System; Ruminant; Anatomia; Animal silvestre; Cervídeo; Sistema Digestório; Ruminante